THE PECULIARITIES OF CADETS’ PSYCHOLOGICAL HEALTH DURING THE COVID-19 PANDEMY - Artyukhova, Vladyslava (PSYCHOLOGICAL JOURNAL, 2020)
The article presents the theoretical analysis of literary sources on the viral epidemic impact on population’s psychological health. The prevailing negative psychological reactions to the pandemic are identified and described, including stress, anger, irritation, anxiety, depression, symptoms of post-traumatic stress disorder and emotional burnout among medical professionals. The need to maintain social distance, limit social contacts, reduced material resources, constantly worn personal protective equipment and other measures have detrimental consequences for people’s psychological well-being and health. A study performed by G.Rubin, S.Wessely found out that behavioral changes acquired by people during quarantine, such as frequent hand washing and avoiding crowds, were becoming new behavioral patterns. K. Brooks, R. K. Webster determined that the duration and uncertainty of quarantine terms were one of the most stressful factors. They noted that uncertainty and quarantine time frame without clear limit were the hallmarks of modern quarantine. It should be noted that the existing studies concerned outbreaks of various epidemics in selected regions with quarantine duration not exceeding 14 days (Xiao etal. Etal., 2020). In addition, the respondents were mostly medical workers or infected people. Today’s pandemic has forced the whole world to be quarantined for more than 4 months, so its psychological consequences have only started to be explored. The relevance of such studies and the increasing number of publications on COVID-19 pandemic issue are emphasized. The article author distinguishes between the concepts of mental and psychological health, considers the approaches to “psychological health”, its criteria and components. The specificity of the presented study lies in its dynamic nature and the determination of transformational changes in various areas of psychological health under the influence of the quarantine measures. The author determined the characteristics of the cadets’ psychological health before the pandemic, and revealed that their health was adaptive in all health areas. A state of mental health determines used behavioral strategies at stress, can act as a resource in the pandemic, on the one hand, but a person’s primary response to any stressors is mental health disorders, on the other one. The data from the study indicate that forced isolation and quarantine restrictions contribute to the emergence of certain transformations of psychological health. They relate mainly to an individual’s interactions with others, corresponding social context, which subsequently acquires several negative characteristics (intolerance to the shortcomings of others, proneness to conflict, aggressiveness, social distance, etc.). During quarantine, a person is forced to adapt to new conditions and act in accordance with them, which requires certain psychological resources. Further research is planned to determine the characteristics of respondents’ subjective attitude to quarantine restrictions, as well as to conduct a more in-depth study of the psychological health and well-being of people after quarantine. In addition, it is advisable to expand the examined sample and cover different age categories.